PERAN SUMBER DAYA MANUSIA UNTUK MENINGKATKAN KREATIVITAS BERWIRAUSAHA - Lestari, Herwiek Diyah; Setiawan, Heri; Zuhaena, Fatwa; Feronika, Trika; Anggraeni , Estetika Ekta (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2025)
The service activity aims to help the Tiga Saudara Mushroom Snack Food Business which is located in Kalikesur Village, Kedungbanteng Subdistrict, Banyumas Regency in empowering its human resources to be more creative in entrepreneurship, so as to produce products that are more profitable. empowering its human resources to be more creative in entrepreneurship, so as to produce products that meet market needs. The method is carried out through mentoring, discussion, skills training, by providing material on the importance of the role of human resources in increasing entrepreneurial creativity. Results showed that based on the identification carried out more role is needed from business actors in order to increase creativity in entrepreneurship. Due to the limited understanding of business actors, the service team provides knowledge about the importance of the role of human resources to increase creativity in entrepreneurship, so that business actors are encouraged to apply and practice their knowledge to be more creative in producing products. so that business actors are encouraged to apply and practice their knowledge to be more creative in producing products, the products they produce are of higher quality, and the products they produce are of higher quality. products produced are of higher quality, the products products produced are able to have differentiators or business characteristics, so that they attract more consumers, and are able to create new markets. attract consumers, and be able to create new markets in the community.